Тепловое излучение взрыва: оценки риска термического поражения людей и возникновения пожаров. I - Stepanov Константин; Stanchits Л.; Stankevich Ю. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
We investigate the hydrodynamic and radiative processes that accompany the explosions of chemical explosives, and fuel-air mixtures. Computer simulation of thermal radiation from fireball of explosion and plume of diffusion combustion of hydrocarbon fuels is performed. The dependences of the heat fluxes from the temperatures and geometrical characteristics of the region occupied by the explosion products and the combustion are determined. The distributions of thermal loads on the targets of different orientations in the vicinity of the zone of energy release are calculated. Comparison of thermal parameters on receivers of radiation with criteria of thermal defeat of people and ignition of combustible materials is lead.